Chinese outward foreign direct investment in Europe - Schüler-Zhou, Yun (Henry Stewart Talks, 2013)
China's outward foreign direct investment, Chinese OFDI, Globalization of Chinese companies, Chinese OFDI in Europe, EU-China investment relationship, Chinese cross-border M&A, Chinese M&A in Europe, Chinese M&A in Germany